(untitled) (International Journal of Ayurveda and Pharma Research, 2022)
In the midst of movement and chaos of life, we forget to pay heed to our health and as a result of which susceptibility to various allergens is increasing day by day. Allergens can be dust, smoke, fumes, pollen and even food. A person can either be allergic to certain allergen right from his birth or can acquire hypersensitivity in later stage of his life. Food allergy is quite common in present era and is affecting the lives of many people. Although there are a number of manifestations of food allergy like nausea, vomiting, diarrhoea, headache etc, most commonly seen are skin manifestations like blisters, itching, redness, burning sensation, oozing, discolouration etc. Acharyas have also mentioned Virudhaahar as one of the most prominent cause of Kushtha. Virudhaahar is any food that causes sensitivity reactions in a person. In contemporary sciences, there are no such permanent cures for hypersensitivity induced skin diseases. But in Ayurveda, through Shodhana and Shamana, these can be treated effectively and occurrence can also be avoided to some extent. This case report is of 38 yrs old male who visited our OPD with itching, oozing, blisters with intense burning sensation in palms and redness and itching in groin areas. The disease was diagnosed here as Charmdala. The treatment protocol opted was Virechan and Shamana. The patient was assessed every 7 days for a month and showed significant relief. This case thus proves that Ayurveda has the potential for curing Virudhaahar janya Kushtha which is often unresponsive to the contemporary treatment protocol.